An exospheric temperature model from CHAMP thermospheric density. Issue 2 (12th February 2017) - Weng, Libin; Lei, Jiuhou; Sutton, Eric; Dou, Xiankang; Fang, Hanxian
Abstract: In this study, the effective exospheric temperature, named as T ∞, derived from thermospheric densities measured by the CHAMP satellite during 2002–2010 was utilized to develop an exospheric temperature model (ETM) with the aid of the NRLMSISE‐00 model. In the ETM, the temperature variations are characterized as a function of latitude, local time, season, and solar and geomagnetic activities. The ETM is validated by the independent GRACE measurements, and it is found that T ∞ and thermospheric densities from the ETM are in better agreement with the GRACE data than those from the NRLMSISE‐00 model. In addition, the ETM captures well the thermospheric equatorial anomaly feature, seasonal variation, and the hemispheric asymmetry in the thermosphere. Key Points: An exospheric temperature model (ETM) was developed The temperature variations in the ETM are characterized as a function of latitude, local time, season, and solar and geomagnetic activities The exospheric temperature and thermospheric densities from the ETM are in better agreement with the GRACE data than those from the NRLMSISE‐00 model